Relações entre eficiência dos gastos públicos com educação e indicadores socioeconômicos: um estudo dos municípios da Região Metropolitana de Fortaleza - Queiroz, Daniele Holanda (2024)
Based on the premise that basic education is the mainstay for the social and economic development of a locality, the general objective of this study is to analyze the relationships between spending on education and the socioeconomic indicators of the municipalities in the Metropolitan Region of Fortaleza. Data Envelopment Analysis (DEA) was adopted to analyze the efficiency of spending on education. The input used was the value of expenses committed to the Education source and the outputs were the IDEB results. Subsequently, we sought to establish relationships with the socioeconomic indicators, namely, population size and average monthly salary of formal workers, through descriptive and inferential statistics. Efficiency is not restricted to the amount invested and effective management of resources is essential. Increasing spending on education alone is not enough to improve socioeconomic indicators. Although the study suggests that municipalities with higher spending on education tend to have larger populations and higher average salaries, this does not imply that increased spending automatically results in greater efficiency or better educational results. It was found that the efficiency of public spending on education is not directly related to the amount spent, but rather to the way these resources are allocated and managed. This reinforces the importance of public policies focused on spending efficiency, rather than simply increasing the budget allocated to education. It is concluded that efficiency is not restricted to the amount invested and that effective management of resources is essential, highlighting that merely increasing spending on education is not enough to improve socioeconomic indicators.